Meningkatan Hasil Belajar PAKBP Melalui Pembelajaran PBL pada Materi Aku Pribadi yang Unik Kelas IV SDS Dakwatul Islam - Desi Lestaria Br Sitepu; Yohanes Subasno; Veronika Sunarningsih (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research is conducted with the aim of improving the learning outcomes of students by using the Problem-Based Learning (PBL) model for the students in grade IV Phase B of SDS DAKWATUL ISLAM in the academic year 2023/2024." The learning outcomes referred to in this research include abilities in the cognitive, affective, and psychomotor domains. The type of research conducted is classroom action research (CAR)." The research design uses the Problem-Based Learning (PBL) model. The subjects of this study are the students in Grade IV Phase B of SDS DAKWATUL ISLAM, which consists of 7 students." The object of the research is the learning outcomes of the students. Data collection techniques utilize both test and non-test methods." The conclusion drawn from this research is that using the Problem-Based Learning (PBL) method can effectively support the learning process, enabling the learning objectives to be achieved successfully."